THE QUALITY OF FROZEN SEMEN DURING STORAGE IN THE MENGWI ARTIFICIAL INSEMINATION SERVICE UNIT, BADUNG REGENCY - Asni, Ni Komang; Bebas, I Wayan; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana; Vol. 14 No. 4 August 2022DO - 10.24843/bulvet.2022.v14.i04.p07, 2022)
The success of artificial insemination in Badung Regency has not been maximized, this can be seen from the number of recurrent mating events. One important factor in the success of artificial insemination is the quality of the frozen semen used. This study aims to determine the quality of frozen semen of Bali cattle stored at different times in the storage depot of the Mengwi Artificial Insemination Service Unit (SPIB), Badung Regency. This study uses frozen bali cattle semen from the Baturiti Regional Artificial Insemination Center. The design used is a completely randomized design with four treatments, namely treatment shortly after arriving at the storage depot (P1), seven days storage time (P2), 14 days (P3) and 28 days (P4). And each treatment consisted of five replications. The observed variables are the percentage of viability, percentage of motility and percentage of intact plasma membrane. The results showed that frozen semen stored in the Mengwi SPIB storage depot was not significantly different (P?0.05) for storage times P1, P2 and P3 but significantly different for storage of 28 days (P4) (P?0.05) with a percentage the average viability of 54.06% up to 61.21%, the percentage of motility 41.39% up to 46.44% and the percentage of the integrity of plasma membrane obtained from 50.53% up to 57.14%. The results of this study can be concluded that the quality of frozen semen spermatozoa both in terms of viability, motility and integrity of plasma membrane decreased significantly on the 28 th day.